Research on the development of technology for the production of emulsion ointment for therapy of cheilitis and analysis of polysaccharides in it - Vishnevska, Lilia; Matsiuk, Oksana (Annals of Mechnikov's Institute, 2023)
Introduction. The problem of the assortment of domestic effective and safe medicines for use in dentistry remains relevant. Despite its widespread prevalence, cheilitis, as a pathology of the oral cavity, is considered insufficiently studied even to this day, as evidenced by clinical and epidemiological studies of some authors, who established the frequency of their occurrence in a wide range (from 6.8 to 30 %). The most common meteorological (44 %) cheilitis. The aim of the work. Experimental studies on the development of technology and determination of control points in the process of production of emulsion ointment for use in cheilitis of various etiologies, as well as analysis of the amount of polysaccharides in it. Materials and methods. The subjects of the study were samples of ointment based on «Phytol» extract, glycerol monostearate, petroleum jelly, polysorbate-80, hydroxyethyl cellulose, sodium benzoate. The research was conducted according to the methods of the State Pharmacopoeia of Ukraine and the Quality Guidelines. Results and discussion. Based on the results of experimental studies, the technology was developed, as well as the determination of control points in the process of production of emulsion ointment for use in cheilitis of various etiologies. The development of the ointment technology was based on the results of previously conducted experimental studies. For the production of emulsion ointment, standard equipment was used, which is necessary in the production of soft medicines. The technology of the emulsion ointment under the conventional name «Phytolung» consists of the following stages: the stage of auxiliary work, the stage of the main technological process (preparation of a solution of hydroxyethyl cellulose with aqueous extract of «Phytol» and sodium benzoate, preparation of the base of the ointment, preparation and homogenization of the ointment), the stage of packing into containers, packing in bundles and group containers for shipment to the warehouse of finished products. In order to scale the developed laboratory technology of emulsion ointment «Phytolung» into industrial production, the critical points of production and conditions of the technological process have been determined, which will allow obtaining finished products of appropriate quality in accordance with the requirements of regulatory documentation. The gravimetric method proved the presence of the number of polysaccharides in the ointment and determined the validation characteristics of the method: precision, correctness and linearity. Conclusions. A technological process to produce an emulsion ointment with the conventional name «Phytolung» in the conditions of a pharmacy and industrial production has been developed, which consists of the following stages: weighing the components of the ointment; preparation of ointment base, obtaining ointment; packaging and labelling of ointment; packing of containers into bundles; packing bundles into boxes. The critical technological parameters of obtaining the drug have been determined. Quantitative determination of the number of polysaccharides was carried out by the gravimetric method and validation characteristics determined that the method is precise, correct and linear. Keywords: ointment, phytoextract, auxiliary substances, production technology, analysis, validation, production control.